Effectiveness of anchor pile protection for metro tunnels under construction disturbances - Lin, Dingxiong; Lin, Ruhui; Zhou, Shaowen; Wang, Hengyu; Xiao, Yongsheng; Bao, Jianjiang; Fei, Li (Geotechnical research, 2025)
This paper analyses the impact of construction disturbances on the effectiveness of anchor pile protection measures for metro tunnels through laboratory experiments and numerical simulations. Artificially disturbed soil was prepared by incorporating salt grains and varying amounts of cement into remoulded silty clay from Ningbo. One-dimensional compression and triaxial tests were conducted to study the engineering properties of both undisturbed and disturbed soils. The relationship between cement content and disturbance degree was established based on compressibility, shear strength, and structural yield stress, providing parameters for the hardening soil model with small-strain stiffness. Disturbance zones were classified using the unloading ratio and field disturbance tests conducted at the Gaotangqiao metro station excavation site. Using PLAXIS 3D, the study analysed the effects of pit excavation–induced and anchor pile construction–induced disturbances on tunnel displacement. The results indicate that at 2% cement content, disturbed soil properties were essentially equivalent to those of undisturbed soil. Pit excavation–induced disturbances increased the tunnel’s maximum vertical displacement by 18.3%. The maximum uplift and horizontal displacements of the tunnel increased by 18% and 17%, respectively, due to anchor pile construction–induced disturbances. Despite these construction disturbances, the anchor pile construction effectively controlled tunnel displacement compared with unmitigated excavation.